Recent Progress of Reclassification of the Genus Streptomyces - Hisayuki Komaki (Microorganisms, 2023)
The genus Streptomyces is a representative group of actinomycetes and one of the largest taxa in bacteria, including approximately 700 species with validly published names. Since the classification was mainly based on phenotypic characteristics in old days, many members needed to be reclassified according to recent molecular-based taxonomies. Recent developments of molecular-based analysis methods and availability of whole genome sequences of type strains enables researchers to reclassify these phylogenetically complex members on a large scale. This review introduces reclassifications of the genus Streptomyces reported in the past decade. Appropriately 34 Streptomyces species were transferred to the other genera, such as Kitasatospora, Streptacidiphilus, Actinoalloteichus and recently proposed new genera. As a result of reclassifications of 14 subspecies, the genus Streptomyces includes only four subspecies at present in practice. A total of 63 species were reclassified as later heterotypic synonyms of previously recognized species in 24 published reports. As strong relationships between species and the secondary metabolite-biosynthetic gene clusters become clarified, appropriate classifications of this genus will not only contribute to systematics, but also provide significant information when searching for useful bioactive substances.